Dissociation Between Incubation of Cocaine Craving and Anxiety-Related Behaviors After Continuous and Intermittent Access Self-Administration - Nicolas, Celine; Russell, Trinity I.; Shaham, Yavin; Ikemoto, Satoshi (Frontiers in Neuroscience, 2022)
Studies using either continuous or intermittent access cocaine self-administration procedures showed that cocaine seeking increases during abstinence (incubation of cocaine craving), and that this effect is higher after intermittent cocaine access. Other studies showed that cocaine abstinence is characterized by the emergence of stress- and anxiety-related states which were hypothesized to increase relapse vulnerability. We examined whether incubation of cocaine craving and anxiety-related behaviors are correlated and whether intermittent cocaine self-administration would potentiate these behaviors during abstinence. Male rats self-administered cocaine either continuously (6 h/day) or intermittently (5 min ON, 25 min OFF x 12) for 14 days, followed by relapse tests after 1 or 21 abstinence days. A group of rats that self-administered saline served as a control. Anxiety-related behaviors were measured on the same abstinence days, using the novelty induced-hypophagia test. Finally, motivation for cocaine was measured using a progressive ratio reinforcement schedule. Lever-presses after 21 abstinence days were higher than after 1 day and this incubation effect was higher in the intermittent access group. Progressive ratio responding was also higher after intermittent cocaine access. Intermittent and continuous cocaine access did not induce anxiety-like responses in the novelty-induced hypophagia test after 1 or 21 abstinence days. Independent of the schedule, incubation of cocaine seeking was not correlated with the novelty-induced hypophagia measures. Results suggest that cocaine-induced anxiety-related states during protracted abstinence do not contribute to incubation of cocaine craving. However, this conclusion is tentative because we used a single anxiety-related measure and did not test female rats.